Comparison of Dexmedetomidine Versus Propofol in Mechanically Ventilated Patients With Sepsis: A Meta-Analysis of Randomized Controlled Trials - Hua-Ze Ding; Yi-Ling Dong; Kai-Yue Zhang; Jia-Yu Bai (Frontiers Media S.A., 2022)
Purpose: The aim of the present study was to evaluate the effects of dexmedetomidine compared with propofol in mechanically ventilated patients with sepsis.Methods: We searched PubMed, EMBASE, and Cochrane Library for randomized controlled trials comparing the effects of dexmedetomidine versus propofol in septic patients requiring mechanical ventilation from inception to December 2021. The primary outcome was 28/30-day mortality and secondary outcomes were ventilator-free days and the length of ICU stay. Pooled relative risk (RR), mean deviation (MD), along with 95% confidence intervals (CI) were used to express outcomes by the software of Review Manager 5.3.Results: Seven studies with a total of 1,212 patients were eligible for meta-analysis. The results primarily showed that dexmedetomidine had no significant effects on the 28/30-day mortality (RR = 1.04 [0.85-1.26], p = 0.70, I2 = 3%). As for secondary outcomes, the administration of dexmedetomidine was not associated with longer-ventilator-free days (MD = 0.50 [−2.15, 3.15], p = 0.71, I2 = 24%) compared with propofol. However, our results revealed dexmedetomidine could shorten the length of ICU stay (MD = −0.76 [−1.34, −0.18], p = 0.01, I2 = 33%).Conclusion: Administration of dexmedetomidine for sedation in septic patients who required mechanical ventilation had no effect on 28/30-day mortality and ventilator-free days, but it could shorten the length of ICU stay.